Movement responses of roe deer to hunting risk. Issue 1 (28th September 2018) - Picardi, Simona; Basille, Mathieu; Peters, Wibke; Ponciano, José Miguel; Boitani, Luigi; Cagnacci, Francesca
ABSTRACT: Large herbivores respond to fluctuations in predation and hunting risk. The temporal scale of risk heterogeneity affects behavioral responses and determines the usefulness of metrics to quantify them. We present a conceptual framework to link anti‐predator responses to risk fluctuations and appropriate metrics, based on temporal scale. We applied this framework to investigate movement responses of roe deer ( Capreolus capreolus ) to hunting risk, measured using movement rate and home range size. Because movements are also affected by reproductive phases, we considered potential effects of the rut in parallel to hunting risk. We compared movements of male and female roe deer in a protected site versus 2 hunted sites during and outside the hunting season and rut. We detected differences in movement rates in response to different hunting management practices. We did not detect effects for hunting regimes or between sexes during the rut when using home range size as the response variable. During the hunting season, movement rates were lower in the hunted sites than in the protected site, irrespective of sex. We did not observe differences in movement rates among sites outside of the hunting season. Males had higher movement rates than females during the rut in only 1 site. Our findings supported the hypothesis that roe deer decrease movements when exposed to high hunting risk. The effect of the rut on movements was negligible except for 1 study site. We suggest that movement rate is a more useful metric than home range size for assessing movement responses to hunting. © 2018 The Wildlife Society Abstract : Large herbivores may respond to predation or hunting by reducing their movements when exposed to risk. To ensure detection of anti‐predator responses, managers should adopt adequate tracking schedules and select appropriate metrics to the temporal scale of risk in the study system.